2017
DOI: 10.3928/01477447-20161013-05
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Is Associated With Time With Provider But Not Clinic Wait Time Among Orthopedic Patients

Abstract: Clinic wait time is considered an important predictor of patient satisfaction. The goal of this study was to determine whether patient satisfaction among orthopedic patients is associated with clinic wait time and time with the provider. The authors prospectively enrolled 182 patients at their outpatient orthopedic clinic. Clinic wait time was defined as the time between patient check-in and being seen by the surgeon. Time spent with the provider was defined as the total time the patient spent in the examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 14 publications
3
27
1
Order By: Relevance
“…Not surprisingly, our findings are consistent with previous literature that has demonstrated wait time to have significant influence on patient satisfaction scores [26,32,33]. There is discordance in the literature as to exactly how a patient's wait time influences satisfaction with provider was more impactful on patient satisfaction scores than actual wait time [34]. Rane et al, however, found that the likelihood of achieving patient satisfaction decreased by 3% for each additional minute of wait time [26].…”
Section: Discussionsupporting
confidence: 90%
“…Not surprisingly, our findings are consistent with previous literature that has demonstrated wait time to have significant influence on patient satisfaction scores [26,32,33]. There is discordance in the literature as to exactly how a patient's wait time influences satisfaction with provider was more impactful on patient satisfaction scores than actual wait time [34]. Rane et al, however, found that the likelihood of achieving patient satisfaction decreased by 3% for each additional minute of wait time [26].…”
Section: Discussionsupporting
confidence: 90%
“…Cultivating and enhancing DPCT is consistent with the Institute of Medicine mandate for patient‐centered care and is also associated with patient satisfaction . For example, time spent with clinician offsets the negative association of spending time in a waiting room . However, the effects of training environments in hematology/oncology on DPCT are not known or appreciated and may be an indicator of educational and patient outcomes alike.…”
Section: Introductionmentioning
confidence: 82%
“…4 For example, time spent with clinician offsets the negative association of spending time in a waiting room. 5 However, the effects of training environments in hematology/oncology on DPCT are not known or appreciated and may be an indicator of educational and patient outcomes alike. Interpersonal and communication skills training is one of seven core competencies recognized by the Accreditation Council for Graduate Medical Education (ACGME) that may be positively or adversely affected by variable training environments.…”
Section: Introductionmentioning
confidence: 99%
“…An a priori power analysis was conducted to determine that approximately 200 patients were needed for inclusion. 11,22 Following Institutional Review Board approval (ORA 15051104), the survey was administered to 212 patients in a single-surgeon, adult reconstruction clinic. The survey was digitally administered on a touch-screen tablet using an electronic independent third party survey center (SurveyMonkey Inc) devoid of any identifying data.…”
Section: Methodsmentioning
confidence: 99%